2014
DOI: 10.1542/peds.2013-3928
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders and Race, Ethnicity, and Nativity: A Population-Based Study

Abstract: OBJECTIVE: Our understanding of the influence of maternal race/ethnicity and nativity and childhood autistic disorder (AD) in African Americans/blacks, Asians, and Hispanics in the United States is limited. Phenotypic differences in the presentation of childhood AD in minority groups may indicate etiologic heterogeneity or different thresholds for diagnosis. We investigated whether the risk of developing AD and AD phenotypes differed according to maternal race/ethnicity and nativity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 57 publications
6
113
0
4
Order By: Relevance
“…Similarly, disparities in access to services and/ or ascertainment and diagnostic bias have been thought to contribute to lower prevalence of ASD without intellectual disability among individuals of migrant background from (Haglund and Kallen 2011;Magnusson et al 2012), a finding observed also in the current study. Our finding of ASD with intellectual disability being more prevalent among children born to migrant parents is in line with recent studies from the USA (Becerra et al 2014), and several European countries (Keen et al 2010;Haglund and Kallen 2011;Magnusson et al 2012;Lehti et al 2013;van der Ven et al 2013;Bolton et al 2014). However, further populationbased studies are needed to disentangle the mechanisms underlying associations between ethnic origin, migration and ASD.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, disparities in access to services and/ or ascertainment and diagnostic bias have been thought to contribute to lower prevalence of ASD without intellectual disability among individuals of migrant background from (Haglund and Kallen 2011;Magnusson et al 2012), a finding observed also in the current study. Our finding of ASD with intellectual disability being more prevalent among children born to migrant parents is in line with recent studies from the USA (Becerra et al 2014), and several European countries (Keen et al 2010;Haglund and Kallen 2011;Magnusson et al 2012;Lehti et al 2013;van der Ven et al 2013;Bolton et al 2014). However, further populationbased studies are needed to disentangle the mechanisms underlying associations between ethnic origin, migration and ASD.…”
Section: Discussionsupporting
confidence: 91%
“…Sell et al (2012) found that African American children had higher rates of object preoccupations and inflexible routines, while Caucasian children demonstrated more unusual sensory stimuli preoccupations and abnormal motor development. Becerra et al (2014) found that ethnic minority children were more likely to display ASD phenotypes with severe emotional outbursts and impaired expressive language than Caucasian children. Consequently, primary care physicians trained to identify typical or common ASD presentations may overlook minority children displaying phenotypic differences.…”
Section: Discussionmentioning
confidence: 96%
“…Besides those variables studied, physician training has been identified as an important variable in ASD diagnosis (Fiscella et al 2014;Fountain et al 2011;Heidgerken et al 2005). Differences in training of physicians serving primarily Caucasian versus African American populations may elucidate group differences, especially given different phenotypic expressions of ASD seen in the literature (Becerra et al 2014;Sell et al 2012). Implicit and explicit bias of physicians serving minority patients would also be worthwhile to study.…”
Section: Discussionmentioning
confidence: 99%
“…Children of migrant parents living in western countries are more likely to have an autism diagnosis than the general population, particularly autism with intellectual disability (Becerra et al 2014;Bolton et al 2014). …”
Section: Introductionmentioning
confidence: 99%